Health care for the elderly - a study on some aspects of non hospital institutions in the city of S. Paulo, Brazil - Bastian, Ernestine M. (Revista de Saúde Pública, 1977)
A survey was done in institutions for elderly people, except in hospitals, in the county of São Paulo, on the number of beds in these homes and aspects of health care offered to their residents. The question was raised whether the number of beds had an influence on health care, in the way that homes with a larger number of beds offered a greater number and more variety of the components of this care. The outcome of the research answered this question positively.